Lake sediments as microplastic sink: The case of three lakes from Northern and Central Poland - Fojutowski, Michał (Quaestiones Geographicae, 2024)
Microplastic (MP) concentrations were determined in surface samples of bottom sediments collected from three lakes in northern and central Poland, located in catchments with low direct anthropopressure. Between 4 MP and 21 MP particles per kilogram of wet sediment were identified in the lakes studied. These values are small compared to those found in lakes located in urbanised areas and other aquatic environments, but important from the point of view of the threat to local freshwater ecosystems. The differences in the number of MP particles in the three examined lakes are a result of the way their nearest environments are used. Lake Czechowskie, the richest in MP particles found, is partially surrounded by pastures and arable lands, while some of the areas lying by are also seasonally used for recreation. In contrast, Lakes Głęboczek and Gościąż, both completely surrounded by forests, show significantly less MP pollution. The sources of MP in these lakes are primarily attributed to atmospheric transport. A correlation was made between the deepest detected MP particles (ranging from 25 cm to 60 cm) and the rate of sedimentation in the lakes, calculated based on the average annual deposition in sediment traps. Based on this, the attempt was made to determine the exact year of the deepest identified MP particles. The results obtained for each lake – the year 1901 for Lake Czechowskie, 1963 for Lake Głęboczek and 1986 for Lake Gościąż – were interpreted in terms of the sources of MP origin.